Common Factors Contributing to the Adjustment Process of Mothers of Children Diagnosed With Down Syndrome: A Qualitative Study. Issue 3 (3rd July 2017) - Korkow-Moradi, Hannah; Kim, Hye Jin; Springer, Nicole P.
ABSTRACT: Grounded theory analysis was used to identify common factors that contributed to the adjustment process of mothers following their child's diagnosis of Down syndrome, and how they ultimately arrived at new perspectives of the diagnosis. Qualitative interviews were conducted and participant narratives were filled with references of: "shock and fear, " "not-knowing, " being negatively impacted by professionals, and encouragement they received from others. The final model included: initial reactions, barriers and buffers, and acquiring a new perspective. Mothers emphasized the benefits of raising a child with an extra chromosome and ultimately experiencing personal "growth" on this parenting journey. Implications for providers who interface with families living with children of Down syndrome were presented.